The Effects of Retrogressive Thaw Slump Development on Persistent Organic Pollutants in Lake Sediments of the Mackenzie River Delta Uplands, NT, Canada - Eickmeyer, David (Université d'Ottawa / University of Ottawa, 2013)
Using a comparative spatial and temporal analysis on sediment cores from 8 lakes in the Mackenzie River Delta uplands region, NT, Canada, this study assessed how persistent organic pollutant (POP) deposition to lake sediments was affected by: (1) the presence of retrogressive thaw slumps on lake shores; and (2) changes occurring with increased autochthonous primary productivity. POPs examined included polychlorinated biphenyls (PCBs), penta- and hexachlorobenzenes (CBzs), and dichlorodiphenyltrichloroethane and metabolites (DDTs). Surface sediments of slump-affected lakes contained higher total organic carbon (TOC)-normalized POP concentrations than nearby reference lakes unaffected by thaw slumps. Inorganic sedimentation rates were positively related to contaminant concentrations, suggesting that the influx of siliciclastic material reducing organic carbon in slump-affected lake water indirectly results in higher concentrations of POPs on sedimentary organic matter. This explanation was corroborated by an inverse relationship between sedimentary POP concentrations and TOC content of the lake water. Deposition proxies of autochthonous carbon were not significantly correlated to POP fluxes of surface sediments, and historical profile fluctuations did not coincide with variation in POP deposition. Thus this study does not support the contention that algal-derived organic carbon increases the delivery of organic pollutants to sediments (the algal-scavenging hypothesis), as previously proposed for mercury. Higher POP concentrations observed in surface sediments of slump-affected lakes are best explained by simple solvent switching processes of hydrophobic contaminants onto a lower pool of available organic carbon when compared to neighbouring lakes unaffected by thaw slump development.